Potential Interactions between the Autonomic Nervous System and Higher Level Functions in Neurological and Neuropsychiatric Conditions - Bassi, Andrea; Bozzali, Marco (Frontiers in Neurology, 2015)
The autonomic nervous system (ANS) maintains the internal homeostasis by continuously interacting with other brain structures. Its failure is commonly observed in many neurological and neuropsychiatric disorders, including neurodegenerative and vascular brain diseases, spinal cord injury, and peripheral neuropathies. Despite the different underlying pathophysiological mechanisms, ANS failure associates with various forms of higher level dysfunctions, and may also negatively impact on patients’ clinical outcome. In this review, we will discuss potential relationships between ANS and higher level dysfunctions in a selection of neurological and neuropsychiatric disorders. In particular, we will focus on the effect of a documented fall in blood pressure fulfilling the criteria for orthostatic hypotension and/or autonomic-reflex impairment on cognitive performances. Some evidence supports the hypothesis that cardiovascular autonomic failure may play a negative prognostic role in most neurological disorders. Despite a clear causal relationship between ANS involvement and higher level dysfunctions is still controversial, this might have implications for neuro-rehabilitation strategies aimed at improving patients’ clinical outcome.